Muscular Response of Females with Kyphosis in Balance Recovery from Postural Perturbation - Hoda Faghfourian (Physical Treatments, 2015)
Purpose: This study aimed to determine muscular response in balance recovery after postural perturbation among females with increased thoracic kyphosis. Methods: This is a quasi-experimental study. A total of 12 female students with thoracic kyphosis (>40 degrees) and 12 matched controls were selected to participate in the study. Each subject underwent unexpected perturbation from anterior, posterior, right, and left directions with eyes open and eyes closed conditions while standing on a movable plate, triggered by a weight equivalent to 10% of the subjects’ body weight. Then, the electromyography activity of some selected muscles was measured. SPSS version 19.0 and Analysis of variance (ANOVAs) with repeated measures were used for data analyses (P<0.05). Results: Significant effects after perturbation were observed with regard to the activation of rectus femoris (P<0.001), biceps femoris (P<0.001), tibialis anterior (P<0.005), gastrocnemius medialis (P=0.032), and gluteus maximus (P<0.001). Whereas, no impact was seen in activities of erector spinae (P=0.461) and rectus abdominal muscles (P=0.224). Also the results showed increase in muscles activities when the eyes is closed compared to open eyes condition (P<0.05). Activities of all muscles were significantly higher in kyphotic group in comparison with control group. However, these differences were statistically significant regarding gastrocnemius medialis (P=0.007), gluteus maximus (P=0.033), and rectus abdominus (P=0.010). Conclusion: Proximal muscles activity was higher in kyphotic subjects than normal subjects during balance recovery after postural perturbation.